The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4103/0019-5049.258058
|View full text |Cite
|
Sign up to set email alerts
|

Integrating perioperative medicine with anaesthesia in India: Can the best be achieved? A review

Abstract: Integrating perioperative medicine with anaesthesia is the need of the hour. Evolution of a new superspeciality called perioperative anaesthesia can improve surgical outcomes by quality perioperative care and guarantee imminent escalation of influence and power for anaesthesiologists. All original peer-reviewed manuscripts pertaining to surgery-specific perioperative surgical home models involving preoperative, intraoperative and postoperative initiatives spanning the past 5 years have been reviewed using PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…The reason for this difference was because the later study included older patients (> 80 years unlike that of > 18 years). On the other hand, the mortality rate was reported from 2.3 to 48.5% for patients undergoing a different type of surgery and heterogeneous study population as well as different severity [8,[23][24][25][26]; indeed the death rate is high for low-income countries because of different reason [10,12], for instance, in America, the overall mortality rate was 0.28% [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for this difference was because the later study included older patients (> 80 years unlike that of > 18 years). On the other hand, the mortality rate was reported from 2.3 to 48.5% for patients undergoing a different type of surgery and heterogeneous study population as well as different severity [8,[23][24][25][26]; indeed the death rate is high for low-income countries because of different reason [10,12], for instance, in America, the overall mortality rate was 0.28% [27].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, female gender, emergency admission, presence of Poly-pharmacy, and the presence of sepsis or in-hospital bloodstream infection were found to be independent predictors of in-hospital death at JUMC. Other studies showed that After adjusting for all co-morbidities, female gender [20,28] while in contrast male gender [11,21] and emergency surgery [8,10,11,21], development of in-hospital complications [7,17,18,22], sepsis [25] was an independent predictor for in-hospital mortality [8,28], but, there was no clear reason for the gender-related increase in mortality. The gender-related discrepancy in predicting mortality might be due to the difference in baseline disease or type of operation (general surgery-coronary artery bypass graft surgery-thoracic surgery) respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been predicted that the evolution of the speciality of 'Perioperative Medicine' can improve surgical outcomes by provision of quality perioperative care and thus improve our visibility and enhance both the influence and power of anaesthesiologists. [ 27 ]…”
Section: The Yangmentioning
confidence: 99%
“…Further, this can also help in integrating perioperative medicine and anaesthesia in an efficient way, which is the need of the hour. [ 5 ]…”
mentioning
confidence: 99%